Lower LDL-cholesterol levels associated with increased inflammatory burden in patients with acute ST-segment elevation myocardial infarction - Açıkgöz,Eser (2021)
SUMMARY OBJECTIVE: Association of low-density lipoprotein cholesterol and highly sensitive C-reactive protein in ST-elevation myocardial infarction patients was assessed in this study. METHODS: 591 consecutive patients who were hospitalized with a diagnosis of ST-elevation myocardial infarction were enrolled and assigned into tertiles according to their serum low-density lipoprotein cholesterol levels. Differences in highly sensitive C-reactive protein among low-density lipoprotein cholesterol tertiles and correlations between highly sensitive C-reactive protein and low-density lipoprotein cholesterol were assessed. RESULTS: Highly sensitive C-reactive protein levels differed significantly among the groups (p<0.001) and found to be highest in the low-density lipoprotein cholesterol tertile 1 and lowest in the low-density lipoprotein cholesterol tertile 3 (post-hoc p-values: tertile 1 vs. 2 <0.001; tertile 1 vs. 3 <0.001; tertile 2 vs. 3=0.019). There was a negative correlation between hs-CRP and both low-density lipoprotein cholesterol (r=-0.332, p<0.001) and total cholesterol (r=-0.326, p<0.001). There was also a negative correlation between highly sensitive C-reactive protein and high-density lipoprotein cholesterol, though the strength of this relationship was weak (r=-0.103, p=0.014). CONCLUSION: Lower low-density lipoprotein cholesterol levels are associated with higher inflammatory burden in patients with acute STEMI. Further studies are required to elucidate the significance of low-density lipoprotein cholesterol levels in ST-elevation myocardial infarction settings.